MENGATASI TEKANAN DI LINGKUNGAN OTOMOTIF: MODERASI SERVANT LEADERSHIP DALAM HUBUNGAN ANTARA STRES KERJA DAN KINERJA KARYAWAN DEALER TOYOTA DI JAKARTA - Al Annafi, Jadi; Cahyaningdyah, Dwi (Jurnal Daya Saing, 2025)
The automotive industry faces significant challenges in a work environment that demands high productivity and optimal service, making it prone to work-related stress that impacts employee performance. This study aims to analyze the influence of work-related stress on employee performance and to examine the role of servant leadership as a moderating variable in the context of Toyota dealership employees in Jakarta. This study employs a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS), involving 137 respondents selected through purposive sampling. The results indicate that work-related stress negatively impacts employee performance, as evidenced by an original sample value of -0.310, a t-statistic value of 2.500, and a P-value of 0.012. However, servant leadership was found to positively and significantly moderate this relationship, with an original sample value of 0.220, a t-statistic value of 2.050, and a P-value of 0.041, indicating that servant leadership can reduce the negative impact of work-related stress on performance.